IMPROVING HUMAN RESOURCESTHROUGH THE INTERNALIZATION OF CULTURAL VALUES ORGANIZATION (Universitas Negeri Semarang, 2015)
Muhammadiyah as an organization hasthe values ofa strong organizational culture. Efforts Muhammadiyah Universities (PTM) is how the culture ofthe organization with the right strategy could predispose Human Resources (HR) professionals and character based on the value of Muhammadiyah. One of the objectivesof this studyare identify the role ofTheory Zand the factors that support the process of internalization of organizational culture in Muhammadiyah Universities. This study uses qualitative research sites at the Muhammadiyah University of Surakarta in Central Java and Universitas Ahmad Dahlan in Yogyakarta. Samples taken are leaders include Vice Rector, the head units such as HR, BIFAS, LPSI as well as lecturers and employees. Internalization process of organizational culture to form employee orientation required three basic elements that support each other, namely: a conducive environment, leadership and exemplary. In this study a conducive environment can be created through the implementation of Theory Z in the field of education that takes into account the following six elements: (1) trust, (2) self-motivation, (3) the reward system, (4) training for enhancing skills, (5) control and shared decision-making as well as (6) quality learning. Activities carried UAD and UMS forinternalization process such as religious activities together, pray, kultum, memorial religious holidays and forms of professional activity as well as other shared ritual that characterize organizations that bring together all employees and lecturers from various faculties and units that exist as an important aspect in creating organizational culture.